PENGARUH KOMUNIKASI ORGANISASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT ZAM-ZAM UTAMA MAKASSAR - Riski Lamato (J-MSDM (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2024)
This research aims to find and produce an analysis of the influence of organizational culture and organizational communication on the performance of PT. Zam-Zam Utama Makassar employees. The respondents in this research were employees who worked within PT Zam-Zam Utama Makassar. The number of respondents sampled in this research was 38 people and was based on a random sampling method. This research uses multiple linear regression analysis techniques or models with the help of SPSS 22 software. Based on the method above, the results of this research show that organizational culture and organizational communication have a significant influence, partially or simultaneously, on employee performance at PT. Zam-Zam Utama Makassar. and the percentage shows that 23.2% of employee performance can be explained by communication and organizational culture.